Comprehensive kinetic analysis and influence of reaction components for chlorzoxazone 6-hydroxylation in human liver microsomes with CYP antibodies. (19th November 2014) - Yamamura, Yoshiya; Koyama, Noriyuki; Umehara, Ken
Abstract: 1. Chlorzoxazone (CLZ) is currently being used as a marker substrate in vitro/vivo studies to quantify cytochrome P450 2E1 (CYP2E1) activity in humans. Although in CLZ 6-hydroxylation several CYPs are responsible, previous studies have presented the monophasicity of the reaction in human liver microsomes (HLMs). Furthermore, the K m values of CYP2E1 for the 6-hydroxylation in HLMs were reported to be lower than those of its recombinant enzymes. 2. This study aimed to provide the comprehensive K m values for the CLZ 6-hydroxylation in HLMs using CYP antibodies. The Eadie–Hofstee plots revealed a biphasic profile and indicate that the reaction was mainly mediated by CYP1A2 as well as CYP2E1. The formation of 6-hydroxychlorzoxazone was more specific for CYP2E1 activity at higher substrate concentration in HLMs. 3. Moreover, KOH as a vehicle for substrate or sucrose included in HLMs preparation had some effect on the activity of CLZ 6-hydroxylase. These constituents seemed to be casually related to the apparent monophasic kinetics and variability in K m values for the CLZ 6-hydroxylation in HLMs. 4. The K m of CYP1A2 and CYP2E1 in HLMs was 3.8 µmol/L and 410 µmol/L, respectively, and the value of CYP2E1 was close to that of recombinant CYP2E1.